(untitled) (Hilo Analítico, 2023)
This critical review is based on the socio-cultural and historical reconstruction carried out by the Venezuelan teacher and researcher Goiz-Eder Calvo, who after research in medicine and philosophy gives a new gender perspective to the world of health sciences and the female body throughout history. For while the stereotype and the social role of women changes and is exposed from different forms of discrimination, the body remains the tool of the female revolution, an additional mechanism of opposition against anatomy as destiny and reproduction as a primary function.